A abordagem funcional dos textos de opinião a partir do uso da tecnologia em sala de aula - Silveira, Danúbia Sampaio Gomes (2020)
The research search investigates the functionality of argumentative genres by analyzing the argumentative strategies used by students in textual productions. Thus, this research observed the construction of oral and written arguments in the debate and opinion article genres. In addition, another technological resource, the whatsapp application, was used to observe how it allows student interaction, promoting discussion and the exchange / sharing of information and knowledge. For this, the theoretical framework that we use is based on studies related to the conception of interactional language defended by Bakhtin (1994); Halliday's (1973) functionalist approach; as well as the conceptions of discursive genre by Rojo (2000), Marcuschi (2008), Bronckart (1999) and Schneuwly & Dolz. (2004). For the analysis of the argumentation we use Koch (1993), Perelman & Olbrechts-tyteca (2000) and Breton (2003). Regarding studies on the insertion of technology in the classroom, we used Lévy (1999), Kensky (2003), Coscarelli (1996), Moran (2013), among others. The research environment involved a 9th grade class from the Municipal School Cesário Lopes de Oliveira de Ordália - District of Itauçu-GO. From a methodological perspective, this research, of a qualitative nature, is characterized as action research, which used the following data collection instruments: participant observation, questionnaires and textual productions in order to reach a result from the triangulation of data. As a result of this research, it was observed that students developed several argumentative strategies based on the exchange of knowledge during the classroom debate and the discussion in the whatsapp group, in addition to producing an opinion article, with constructions from a critical point of view, with the insertion of new knowledge and the ability to argue through convincing and persuasive strategies. As an educational product, in addition to a blog with orientations, doubts and questions about the genres of an argumentative nature, it was created an activity notebook with the title: “Activity notebook about working with argumentation from a functionalist perspective.”. The purpose of the material is to offer other professionals and scholars in the field, a suggestion of work from a functionalist perspective on argumentative genres and the use of the whatsapp application as a means of teaching / learning.